2012
DOI: 10.1007/s10578-012-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Psychotic Experiences in Kenyan Children and Adolescents

Abstract: Psychotic-like experiences (PLEs) have been observed worldwide in both adults and children outside the context of a clinical disorder. In the current study, we investigate the prevalence and patterns of PLEs among children and adolescents in Kenya. Among 1,971 students from primary and secondary schools around Nairobi (aged 8–19), 22.1 % reported a lifetime history of a psychotic experience, and 16.3 % reported this unrelated to sleep or drugs. Psychotic experiences were more common in males compared to female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
3
28
2
Order By: Relevance
“…In terms of mean differences, the male respondents had higher scores on the Brief CAPE-P10 and its subscales. Mamah et al (2013) reported a similar finding in a cross-sectional sample of 1971 Kenyan adolescents.…”
Section: Discussionsupporting
confidence: 65%
“…In terms of mean differences, the male respondents had higher scores on the Brief CAPE-P10 and its subscales. Mamah et al (2013) reported a similar finding in a cross-sectional sample of 1971 Kenyan adolescents.…”
Section: Discussionsupporting
confidence: 65%
“…Four of the five childhood PLE profiles ( None , Moderate , Hallucinatory , and Strong ) were previously also identified in studies employing LCA on lifetime symptoms from interviews of adolescent and adult samples. In those, 83–93% of individuals were classified into a ‘normal’ class (Gale et al ., ; Mamah et al ., ; Ndetei et al ., ; Pignon et al ., ; Shevlin et al ., ), whereas 57.1% of children were classified into two classes characterized by high probabilities of responding Not True to all items ( None; 27.4% of children) or all but three items ( Minor ; 29.7% ) . The differentiation of the None and Minor classes in our sample is unlikely to reflect over‐fitting of the LCA model, as Minor emerged already in the 4‐class solution with None , Moderate , and Strong (i.e., before Hallucinatory in the 5‐class model).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the other three classes delineated profiles characterized by more prominent endorsement of PLEs and robust (medium‐to‐large) independent associations with each psychopathology. Greater proportions of children were classified in each of these three classes relative to adolescent and adult samples (Gale et al ., ; Mamah et al ., ; Ndetei et al ., ; Pignon et al ., ; Shevlin et al ., ), but the consistency of these class types across all samples suggests that they may endure across developmental periods (though longitudinal data are required to confirm this hypothesis). Two classes ( Moderate and Strong ) showed consistent patterns of responding across all nine PLE items that differed from each other quantitatively rather than qualitatively, akin to the ‘intermediate’ and ‘psychosis’ classes described by Shevlin et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Assessing clinical risk early has significantly advanced the possibility of indicated prevention of full-blown psychotic disorders (Yung et al 1996(Yung et al , 2004Miller et al 1999). Our group has conducted multiple studies in Kenya, investigating the prevalence of PLEs and risk for developing illness using self-report questionnaires (Mamah et al , 2013Ndetei et al 2012;Owoso et al 2014). The Washington Early Recognition Center Affectivity and Psychosis (WERCAP) Screen ) was developed to overcome some of the challenges in assessing risk of developing psychotic disorders, guided by the existing literature on risk assessment and our previous efforts in Africa and the USA.…”
Section: Introductionmentioning
confidence: 99%